Lost in translation : present-day terms in the maintenance texts of the nadi?tu from old Babylonian Nippur - Van Wyk, Susandra J. (Journal for semitics, 2014)
Present-day terms such as the usufruct - in civil law systems - and its equivalent, the life-right - in common law systems - were foreign to ancient Near Eastern legal texts. Prima facie both terms - usufruct and life-right - direct the "time-limited interest" of the use and enjoyment by a person over the property of another. However, mainstream ancient Near Eastern scholars' unqualified use of the foreign terms - diverged in time and space - affect the translation and our insight into ancient texts. In addition, differences in land ownership institutions and philosophies in present-day law systems and those of ANE contribute to variances in the meaning and interpretation of the intrinsic aspects of property and as such "time-limited interest" applicable: a usufruct, life-right or even a hybrid form of both. In the article, I focus on the maintenance - a time-limited interest - of the nad?tu priestess in the Old Babylonian city-state of Nippur. The application of Stone's theory on Nippur's land ownership - the institutions' economy - prima facie shows that the nadi?tu of Nippur held a freestanding life-right, rather than a usufruct which the majority of ANE scholars assigned to the nadi?tu's maintenance. However, I propose a deviation with the superficial overlay of present-day terms on the maintenance of the nadi?tu by presenting a time-limited interest framework. The framework serves as a delineation method of identifying the characteristics of the maintenance-construction of the nadi?tu from OB Nippur: communicating a "unitary concept" in context of the ancient texts - rather than only assigning coined terms - taking recognition of the influences of Nippur's land ownership philosophy.